FORMULASI KEBIJAKAN UPAH MINIMUM KOTA YOGYAKARTA - , SATRIA ADI GUNAWAN; , Dr.Ambar Widaningrum, M.A ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study discuss the minimum wage policy formulation framework Yogyakarta. This policy is done to solve the problem of labor wages, which are considered weak in its implementation and also to better satisfy the justice of the workers. The main argument put more towards the policy formulation process in terms of a political than technocratic terms. This research direction to seek clarity and track the minimum wage policy formulation for the city of Yogyakarta in 2013. Limitation of this study is the concept of public policy formulation stage, the actor who played the role, and interests of actors in each stage. This thesis uses descriptive qualitative method of analysis. Techniques of data collection with in-depth interviews with actors associated with policy formulation, inspection documents, observation, and an understating of documentation. Researchers compared the practices that occur in the theory, and then perform a descriptive analysis and discussion. Values and interests of actors who brought the policy depends on the background actors who become representatives in Depeko. Quality of Yogyakarta minimum wage policy in terms of the policy process is still the same as the previous policy, because the determination was still glued to the legislation on it. In terms of content more projustice for workers because the nominal set higher than the previous policy standards. Suggestions is local government must be innovate in the formulation of the rules of the city minimum wage policy, so that the minimum wage policy is decided based the conditions of a real diverse area. Then, goverment need for improvement in all sectors related directly or indirectly to the minimum wage policy. Basically wage is one component in the production of a company.So instead of that, the determination of Minimum Wage of Yogyakarta should be directed to protect the workers/laborers by take notice the level of capability and performance the company, so that employees/workers can prosper, but companies can flourish and sustainable